Vibrational analysis of Li₁₊ₓAlₓTi₂₋ₓ(P0₄)₃ (0.0 < x < 0.5) glass ceramic electrolytes prepared by acetic acid-assisted sol-gel method / Maziidah Hamidi … [et al.] - Hamidi, Maziidah; Mohamed, S. N.; Raja Mustapha, Raja Ibrahim Puter; Hassan, Oskar Hasdinor; Yahya, Muhd Zu Azhan (Institute of Research Management and Innovation (IRMI), 2015)
In this study, Li₁₊ₓAlₓTi₂₋ₓ(P0₄)₃ (0.0 < x < 0.5) was prepared by acetic acid-assisted sol-gel method The structural properties of NASICON phosphates material with chemical formula LiTi₂(P0₄)₃ were observed using the Fourier transform infrared spectroscopy. NASICON is a family of crystalline phosphate with a general network system consisting of P0₄ tetrahedra, thus bands were assigned by vibrations contributed by basic phosphates, in the wavenumber region between 1300 cm1 and 600 cm1. Experimental spectra indicated that all Li₁₊ₓAlₓTi₂₋ₓ(P0₄)₃ (0.0 < x < 0.5), heat treated at 600°C and 700°Cfor 3 hours in air, samples showed the presence of phosphate peaks with shift in frequency asAl3⁺ is substituted into the structure, and with increasing temperatures. Some bands broadened and overlapped causing it hard to analyze the arising bands. It however determined the existence of NASICON structure in all of the samples under study.